Modified hard carbon material and preparation method thereof, hard carbon fusion material, negative pole piece, battery and electric equipment

By coating the soft carbon material cladding layer on the hard carbon substrate, the modified hard carbon material is prepared, and the side reaction problems caused by the defective structure of the hard carbon material are solved, the efficiency and power characteristics of the battery are improved, and the accuracy of the charge state monitoring of lithium batteries is improved.

CN119542368APending Publication Date: 2025-02-28CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311123525.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

During the mass production and preparation of hard carbon materials, a large number of defective structures are generated, resulting in side reactions with the electrolyte, reducing the first-time Coulomb efficiency and power characteristics of the battery. At the same time, the discharge process of graphite negative electrode is not easy to detect.

Method used

Modified hard carbon material is used, which uniformly coats the soft carbon material coating layer on the hard carbon substrate to form a stable core-shell structure, reduces the proportion of defective structures, and prepares the material through wet fusion and carbonization treatment.

Benefits of technology

It effectively reduces the side reaction between modified hard carbon materials and electrolyte, improves the first-time Coulomb efficiency and power characteristics of the battery, and improves the OCV recognition of lithium batteries and the accuracy of SOC monitoring and measurement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542368A_ABST
    Figure CN119542368A_ABST
Patent Text Reader

Abstract

The invention provides a modified hard carbon material and a preparation method thereof, a hard carbon fusion material, a negative pole piece, a battery and electric equipment, the modified hard carbon material comprises a hard carbon substrate and a coating layer, the hard carbon substrate exists in a solid form at normal temperature, the coating layer coats the outer surface of the hard carbon substrate, so that the hard carbon substrate and the coating layer form a core-shell structure, and the core-shell structure is formed by the hard carbon substrate and the coating layer. The modified hard carbon material meets the structure, so that the surface structure of the hard carbon substrate can be improved by the coating layer, side reaction is reduced, and the power characteristic of the battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and specifically to a modified hard carbon material and a preparation method thereof, a hard carbon fusion material, a negative electrode sheet, a battery and an electrical device. Background Art

[0002] Lithium batteries have high charge and discharge performance and are widely used in products such as electric vehicles. On-board battery management systems usually use open circuit voltage (OCV) to estimate the state of charge (SOC) of lithium batteries. However, the voltage curve of lithium batteries with graphite as the negative electrode changes significantly near the end of discharge, and it is easy to lose power seriously at the end of discharge, which reduces the user experience. At the same time, the interlayer spacing of graphite is low, which restricts the diffusion of lithium ions; the low-temperature performance of negative electrode graphite is poor and cannot meet the low-temperature performance requirements.

[0003] The voltage distinction of the slope section of the charge and discharge curve of hard carbon materials is obvious. After adopting the hard carbon negative electrode system, the recognition of the open circuit voltage of lithium batteries can be significantly improved, and the monitoring measurement error of the battery state of charge can be reduced. However, a large number of defect structures will be generated in the mass production process of hard carbon materials. These defect structures will react with the electrolyte, resulting in low coulomb efficiency in the first formation process, and the contribution of the above defect structures to the power characteristics is negligible. Summary of the invention

[0004] The purpose of the present application is to provide a modified hard carbon material and its preparation method, a hard carbon fusion material, a negative electrode plate, a battery and an electrical device, which solves the problem that the defective structure of the hard carbon material accounts for a large proportion and causes side reactions, and the problem that the discharge process of the graphite negative electrode is difficult to detect.

[0005] To achieve the purpose of this application, this application provides the following technical solutions:

[0006] In a first aspect, the present application provides a modified hard carbon material, comprising: a hard carbon substrate, existing in a solid form at room temperature; a coating layer, the coating layer coating the outer surface of the hard carbon substrate, the coating layer having a thickness of 1nm-40nm.

[0007] In one embodiment, the coating layer is a soft carbon material, the carbon layer structure of the coating layer is a disordered carbon layer stack, and the carbon layer spacing of the coating layer is 0.34nm-0.37nm.

[0008] In one embodiment, the particle size D50 of the modified hard carbon material is 3.5 μm-8.5 μm; and / or

[0009] The tap density of the modified hard carbon material is 0.6 g / cm 3 -0.9g / cm 3 ; and / or

[0010] The specific surface area of ​​the modified hard carbon material is 2.5 m 2 / g-4.0m 2 / g.

[0011] In the second aspect, the present application also provides a hard carbon fusion material, including: a hard carbon precursor, which exists in solid form at room temperature; a coating layer precursor, which exists in liquid form at room temperature, and the coating layer precursor is coated on the outer surface of the hard carbon precursor, and the mass ratio of the hard carbon precursor to the coating layer precursor is 1:(0.02-0.06); the hard carbon fusion material is carbonized to form a modified hard carbon material as described in any embodiment of the first aspect, wherein the hard carbon precursor forms a hard carbon substrate after carbonization, and the coating layer precursor forms a coating layer after carbonization.

[0012] In one embodiment, the particle size D50 of the hard carbon precursor is 3 μm-8.56 μm; and / or

[0013] The tap density of the hard carbon precursor is 0.85 g / cm 3 -1g / cm 3 ; and / or

[0014] The specific surface area of ​​the hard carbon precursor is 2 m 2 / g-4m 2 / g.

[0015] In one embodiment, the density of the nano precursor is 1.05 g / cm 3 -1.25g / cm 3 ; and / or

[0016] The coking value of the nano precursor is 12%-24%; and / or

[0017] The ash content of the nano precursor is less than or equal to 0.15%; and / or

[0018] The water content of the nano precursor is less than or equal to 0.3%.

[0019] In a third aspect, the present application also provides a method for preparing a modified hard carbon material, comprising: mixing a coating layer precursor with a hard carbon precursor to obtain a hard carbon fusion material; carbonizing the hard carbon fusion material to obtain a modified hard carbon material, wherein the hard carbon precursor forms a hard carbon substrate after carbonization, and the coating layer precursor forms a coating layer after carbonization.

[0020] In one embodiment, the mixing time of the coating layer precursor and the hard carbon precursor is 5 min-40 min, and the mixing rotation speed of the coating layer precursor and the hard carbon precursor is 200 r / min-1500 r / min.

[0021] In one embodiment, the hard carbon fusion material is carbonized in an inert atmosphere at a temperature of 800° C.-1450° C. and for a time of 5 h-22 h.

[0022] In a fourth aspect, the present application also provides a negative electrode plate, comprising a negative electrode current collector and the modified hard carbon material described in any one embodiment of the first aspect, or comprising a negative electrode current collector and the modified hard carbon material prepared according to any one embodiment of the third aspect, wherein the modified hard carbon material is attached to the negative electrode current collector.

[0023] In a fifth aspect, the present application further provides a battery, comprising a positive electrode sheet, a separator and the negative electrode sheet described in the fourth aspect, wherein the positive electrode sheet and the negative electrode sheet are stacked, and the separator is placed between the positive electrode sheet and the negative electrode sheet.

[0024] In a sixth aspect, the present application also provides an electrical device, comprising the battery described in the fifth aspect.

[0025] In the modified hard carbon material provided in the present application, the coating layer is uniformly coated on the outer surface of the hard carbon substrate, so that the hard carbon substrate and the coating layer constitute a stable core-shell structure. The coating layer covers the defect structure of the hard carbon substrate, reduces the proportion of defect structures on the outer surface of the modified hard carbon material, and forms a uniform carbon coating structure, which is beneficial to reduce the side reactions between the modified hard carbon material and the electrolyte, reduce the consumption of lithium ions, and improve the initial coulomb efficiency of the battery; at the same time, after the hard carbon material is introduced into the negative electrode of the lithium battery, the voltage of the slope section of the charging and discharging curve of the lithium battery is clearly distinguished, which can significantly improve the battery OCV recognition, reduce the SOC monitoring measurement error, and ensure the user experience. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 is the surface morphology of the modified hard carbon material of Example 1 of the present application;

[0028] Figure 2 is a flow chart for preparing a modified hard carbon material according to an embodiment;

[0029] Figure 3 is a SOC-OCV curve of a modified hard carbon material and graphite according to an embodiment. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0031] It should be noted that when a component is said to be "fixed to" another component, it can be directly on the other component or there can be a central component. When a component is said to be "connected to" another component, it can be directly connected to the other component or there can be a central component at the same time.

[0032] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this application and in the specification are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more of the related listed items.

[0033] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0034] The present application embodiment provides a modified hard carbon material, please refer to Figure 1 The hard carbon material includes a hard carbon substrate and a coating layer, wherein the hard carbon substrate exists in a solid form at room temperature, the room temperature is 10°C-30°C, and further, the room temperature is 20°C-25°C, and the coating layer is coated on the outer surface of the hard carbon substrate.

[0035] The hard carbon substrate has a disordered carbon layer or a carbon layer structure with a large interlayer spacing, which is conducive to the diffusion of lithium ions and stability during the cycle process to improve the power characteristics of the battery. The carbon interlayer spacing of the hard carbon substrate is 0.37nm-0.39nm. Specifically, the carbon interlayer spacing of the hard carbon substrate can be 0.372nm, 0.375nm, 0.377nm, 0.385nm, etc.

[0036] There are a large number of defect structures (such as micropores) and oxygen-containing functional groups on the outer surface of the hard carbon substrate, which are prone to side reactions with the electrolyte, resulting in low initial coulombic efficiency and large irreversible capacity of the battery made of the hard carbon substrate. The coating layer is evenly coated on the outer surface of the hard carbon substrate, so that the defect structures and oxygen-containing functional groups on the outer surface of the hard carbon substrate are covered by the coating layer, and the hard carbon substrate and the coating layer form a stable core-shell structure and form a modified hard carbon material.

[0037] The coating layer covers the defective structure and oxygen-containing functional groups on the outer surface of the hard carbon substrate, reducing the proportion of defective structures and oxygen-containing functional groups on the outer surface of the modified hard carbon material and forming a uniform carbon coating structure. Compared with the hard carbon substrate, the modified hard carbon material has fewer side reactions with the electrolyte, which is beneficial to improving the first coulomb efficiency of the battery; at the same time, the coating layer covers the hard carbon substrate, which is also beneficial to improving the power characteristics of the battery made of the modified hard carbon material, that is, it can significantly improve the OCV recognition of graphite negative electrode batteries, especially lithium iron phosphate-graphite batteries, and reduce SOC monitoring measurement errors.

[0038] Specifically, the coating layer is a soft carbon material, and the carbon layer structure of the coating layer is a disordered carbon layer stack, with a carbon layer spacing of 0.34nm-0.37nm. The coating layer has a relatively small pore structure, which can not only fill the defect structure of the hard carbon substrate, but also cover the functional groups on the surface of the hard carbon substrate, reduce the side reactions between the modified hard carbon material and the electrolyte, and reduce the lithium ions consumed in forming the SEI (Solid Electrolyte Interface) membrane, thereby improving the first coulomb efficiency of the battery; at the same time, the formed SEI membrane is in contact with the flat coating surface, and has better contact interface stability, so that the SEI membrane has better stability at high temperature or after long-term use, improves the high temperature performance of the battery, and is also conducive to the diffusion of lithium ions at the SEI membrane, improving the rate performance of the battery; thereby improving the battery OCV recognition and reducing the SOC monitoring measurement error.

[0039] The thickness of the coating layer is 1 nm-40 nm, preferably, the thickness of the coating layer is 2 nm-20 nm, specifically, the thickness of the coating layer can be 3 nm, 10 nm, 15 nm, 20 nm, etc.

[0040] By making the thickness of the coating layer meet the above range, it is beneficial to reasonably set the thickness of the coating layer and realize the coating layer fully covers the outer surface of the hard carbon substrate. Below the above range, the thickness of the coating layer is small, the coating layer has poor coating ability on the outer surface of the hard carbon substrate in some areas, the defective structure of the hard carbon substrate is exposed, and side reactions are more likely to occur; exceeding the above range, the thickness of the coating layer is large, which hinders the diffusion of lithium ions in the modified hard carbon material and affects the electrochemical performance.

[0041] In one embodiment, the particle size D50 of the modified hard carbon material is 3.5 μm-8.5 μm, preferably, the particle size D50 of the modified hard carbon material is 5.5 μm-6.5 μm, wherein the particle size D50 of the modified hard carbon material is the particle size corresponding to when the cumulative particle size distribution number of the modified hard carbon material reaches 50%.

[0042] By making the particle size D50 of the modified hard carbon material meet the above range, the average particle size of the modified hard carbon material is within a reasonable range, avoiding the particle size of the modified hard carbon material being too large or too small. Below the above range, the particle size of the modified hard carbon material is too small, the larger the specific surface area of ​​the modified hard carbon material in contact with the electrolyte, the more charge is consumed during the charge and discharge process, and the greater the irreversible capacity loss of the battery; exceeding the above range, the particle size of the modified hard carbon material is too large, and processing problems such as scratching during the coating process are prone to occur, affecting the performance of the battery.

[0043] In one embodiment, the tap density of the modified hard carbon material is 0.6 g / cm 3 -0.9g / cm 3 Preferably, the tap density of the modified hard carbon material is 0.7 g / cm 3 -0.8g / cm 3 The tap density in the above range is beneficial to increase the compaction density and porosity of the modified hard carbon material when preparing the pole piece, which is beneficial to balance the energy density and power performance of the battery.

[0044] In one embodiment, the specific surface area of ​​the modified hard carbon material is 2.5 m 2 / g-4m 2 / g, preferably, the specific surface area of ​​the modified hard carbon material is 3m 2 / g-3.5m 2 / g. The appropriate comparative area is beneficial to balance the liquid absorption and side reactions of the modified hard carbon material, thus obtaining a battery with better rate and cycle performance.

[0045] The present application also provides a hard carbon fusion material, which includes a hard carbon precursor and a coating layer precursor, wherein the hard carbon precursor exists in a solid form at room temperature, and the coating layer precursor exists in a liquid form at room temperature, and after the hard carbon precursor and the coating layer precursor are mixed, the coating layer precursor is coated on the outer surface of the hard carbon precursor. After carbonization, the hard carbon fusion material forms the modified hard carbon material described in any one of the above embodiments.

[0046] The hard carbon precursor forms a hard carbon substrate after carbonization, and the hard carbon precursor exists in a solid form at room temperature.

[0047] The hard carbon precursor in the present invention is a raw material for preparing a hard carbon substrate, and can be at least one of biomass, phenolic resin, and coal tar used to prepare a hard carbon material body; the hard carbon precursor in the present invention can also be a hard carbon material body, and the hard carbon material body forms a hard carbon substrate after carbonization. Among them, the hard carbon material body is hard carbon obtained by carbonization of biomass, phenolic resin, coal tar, etc. The hard carbon substrate formed by carbonization of the hard carbon material body has a more stable carbon layer structure and less impurities than the hard carbon substrate (biomass, phenolic resin, coal tar, etc.) formed by the former, and thus has better performance, which is preferred in the present invention. The coating layer precursor forms a coating layer after carbonization. The coating layer precursor exists in liquid form at room temperature and has fluidity. The coating layer precursor can be a conventional product in the petroleum refining process, such as a by-product in the petroleum refining process. Optionally, the coating layer precursor includes at least one of petroleum residual oil and coal tar pitch.

[0048] Optionally, the hard carbon precursor and the coating layer precursor are mechanically mixed so that the coating layer precursor is coated on the surface of the hard carbon precursor.

[0049] The coating layer precursor exists in liquid form at room temperature. During the mechanical mixing process, the coating layer precursor can enter the coating layer pore structure in the hard carbon precursor and fill it evenly, and adhere to the surface of the hard carbon precursor, achieving an excellent coating effect on the hard carbon precursor, which is beneficial to reducing the defect structure on the surface of the hard carbon precursor, thereby reducing the side reaction between the hard carbon substrate formed by the hard carbon precursor and the electrolyte, and increasing the initial charge and discharge efficiency of the modified hard carbon material.

[0050] If a solid coating layer precursor and a hard carbon precursor are mixed, since the solid coating layer precursor exists in a solid form at room temperature and has no fluidity, it cannot enter the defective parts of the hard carbon precursor. During the mechanical mixing process, the solid coating layer precursor mainly contacts and coats the hard carbon particles of the hard carbon precursor at the physical point interface, and some micron-level particles of the solid coating layer precursor modify the surface microscopic coating layer structure of the hard carbon precursor and cannot enter the internal micropores of the hard carbon precursor to fill, which will result in poor coating effect of the solid coating layer precursor on the hard carbon precursor.

[0051] Optionally, the coating layer precursor is petroleum residue oil, which exists in liquid form at room temperature. The mechanical mixing process can enter the interfacial pore structure of the hard carbon precursor and fill it evenly. Moreover, the residual carbon rate of petroleum residue oil is relatively high and the content of oxygen-containing functional groups is relatively low, which can modify the oxygen-containing functional groups on the surface of the hard carbon precursor and achieve an excellent coating effect.

[0052] In one embodiment, in the hard carbon fusion material, the mass ratio of the hard carbon precursor to the coating layer precursor is 1:(0.02-0.06), preferably, the mass ratio of the hard carbon precursor to the coating layer precursor is 1:(0.02-0.04).

[0053] In one embodiment, the particle size D50 of the hard carbon precursor is 3.5 μm-8.5 μm. Preferably, the particle size D50 of the hard carbon precursor is 5.5 μm-6.5 μm. The particle size D50 of the hard carbon precursor is the particle size corresponding to when the cumulative particle size distribution number of the hard carbon precursor reaches 50%.

[0054] In one embodiment, the tap density of the hard carbon precursor is 0.85 g / cm 3 -1g / cm 3 Preferably, the tap density of the hard carbon precursor is 0.9 g / cm 3 -0.95g / cm 3 .

[0055] In one embodiment, the specific surface area of ​​the hard carbon precursor is 2 m 2 / g-4m 2 / g. Preferably, the specific surface area of ​​the hard carbon precursor is 2.4m 2 / g-3.5m 2 / g.

[0056] In one embodiment, the density of the coating layer precursor is 1.05 g / cm 3 -1.25g / cm 3 Preferably, the density of the coating layer precursor is 1.1 g / cm 3 -1.2g / cm 3 .

[0057] In one embodiment, the coking value of the coating layer precursor is 12%-24%. Preferably, the coking value of the coating layer precursor is 15%-20%.

[0058] In one embodiment, the ash content of the coating layer precursor is less than 0.15%. Preferably, the ash content of the coating layer precursor is less than 0.05%.

[0059] In one embodiment, the water content of the coating layer precursor is less than 0.3%. Preferably, the water content of the coating layer precursor is less than 0.1%.

[0060] This application also provides a method for preparing a modified hard carbon material, see Figure 2 , the preparation method of the modified hard carbon material comprises:

[0061] Step S10: mixing the coating layer precursor and the hard carbon precursor to obtain a hard carbon fusion material;

[0062] Step S20: carbonizing the hard carbon fusion material to obtain a modified hard carbon material, wherein the hard carbon precursor is carbonized to form a hard carbon substrate, and the coating layer precursor is carbonized to form a coating layer.

[0063] The hard carbon precursor can be at least one of biomass, phenolic resin, and coal tar pitch; the hard carbon precursor can also be a hard carbon material body; preferably, a hard carbon material body; the coating layer precursor includes at least one of petroleum residue oil and coal tar pitch. The coating layer precursor can be a by-product of the petroleum refining process and does not require dissolution treatment using chemical solvents. It can be directly mechanically mixed with the hard carbon precursor. The coating process is simple and the product is easy to mass produce.

[0064] Optionally, in the above step S10, the coating layer precursor and the hard carbon precursor are mixed by wet fusion, the equipment used for wet fusion is a mechanical fusion machine, and the mass ratio of the hard carbon precursor to the coating layer precursor is 1:(0.02-0.06), preferably, the mass ratio of the hard carbon precursor to the coating layer precursor is 1:(0.02-0.04). Specifically, the mass ratio of the hard carbon precursor to the coating layer precursor can be 1:0.02, 1:0.03, 1:0.04, etc.

[0065] In the above step S10, the amount of coating layer precursor added can be controlled to control the coating amount of the hard carbon substrate; the rotation speed of the wet fusion equipment and the time of the wet fusion can be controlled to control the degree of rounding of the coating layer formed by the coating layer precursor, so that the surface of the hard carbon precursor is impregnated, melted and physically modified by the coating layer precursor, and the structure of the coating layer has high controllability and excellent uniformity.

[0066] Optionally, in the above step S20, the hard carbon fusion material is carbonized under a constant temperature condition.

[0067] Optionally, after the above step S20, the modified hard carbon material obtained after the carbonization treatment is mixed in a mixer, and then screened and discharged. During the carbonization process of the hard carbon fusion material, the sintering degree of the hard carbon fusion material at different positions is different, so that the physical and chemical properties of the hard carbon fusion material at different positions after carbonization are different. Mixing the modified hard carbon material obtained after the carbonization treatment can improve the consistency of the modified hard carbon material.

[0068] In one embodiment, the coating layer precursor and the hard carbon precursor are mixed for 5-40 minutes, preferably, the coating layer precursor and the hard carbon precursor are mixed for 20-60 minutes. Specifically, the coating layer precursor and the hard carbon precursor can be mixed for 10 minutes, 15 minutes, 20 minutes, 30 minutes, etc.

[0069] The coating layer precursor and the hard carbon precursor are mixed by wet fusion. The rotation speed of the equipment used for wet fusion is 200r / min-1500r / min. The hard carbon fusion material exists in the form of a solid-liquid mixture at room temperature, that is, at room temperature, the solid hard carbon precursor and the liquid coating layer precursor exist in a solid-liquid mixture. Specifically, the rotation speed of the equipment used for wet fusion can be 300r / min, 600r / min, 900r / min, 1200r / min, etc.

[0070] In one embodiment, the hard carbon fusion material is carbonized in an inert atmosphere of a tunnel kiln device, the carbonization temperature is 800°C-1450°C, and the carbonization time is 5h-22h. Preferably, the carbonization temperature is 900°C-1350°C, and the carbonization time is 10h-20h.

[0071] Specifically, the temperature of the carbonization treatment can be 950°C, 1000°C, 1100°C, 1200°C, 1300°C, etc.; the time of the carbonization treatment can be 10h, 15h, 18h, 20h, etc.

[0072] In one embodiment, the modified hard carbon material obtained after the carbonization treatment is mixed in a mixer, and the mixing time is 10min-80min, preferably, the mixing time is 30min-50min. Specifically, the mixing time can be 30min, 35min, 40min, 45min, 50min. Mixing the modified hard carbon material is conducive to improving the carbonization uniformity of the modified hard carbon material.

[0073] The present application also provides a negative electrode plate, comprising a negative electrode current collector and the modified hard carbon material described in any one of the above embodiments, or comprising a negative electrode current collector and a modified hard carbon material obtained by the preparation method of the modified hard carbon material described in any one of the above embodiments, wherein the modified hard carbon material is attached to the negative electrode current collector.

[0074] It can be understood that the negative electrode plate in this embodiment has the modified hard carbon material in the above-mentioned embodiment. Therefore, the negative electrode plate in this embodiment has all the technical effects of the modified hard carbon material in the above-mentioned embodiment. Since the technical effects of the modified hard carbon material have been fully explained in the above-mentioned embodiment, they will not be repeated here.

[0075] The present application also provides a battery, comprising a positive electrode sheet, a separator and the above-mentioned negative electrode sheet, the positive electrode sheet and the negative electrode sheet are stacked, and the separator is placed between the positive electrode sheet and the negative electrode sheet.

[0076] It can be understood that the battery in this embodiment has the negative electrode plate in the above embodiment. Therefore, the battery in this embodiment has all the technical effects of the negative electrode plate in the above embodiment. Since the technical effects of the negative electrode plate have been fully explained in the above embodiment, they will not be repeated here.

[0077] The present application also provides an electrical device, comprising the battery described in the above embodiment.

[0078] It can be understood that the electrical equipment in this embodiment has the battery in the above embodiment. Therefore, the electrical equipment in this embodiment has all the technical effects of the battery in the above embodiment. Since the technical effects of the battery have been fully explained in the above embodiment, they will not be repeated here.

[0079] The technical solution of the present invention is described in detail below through specific embodiments.

[0080] The hard carbon precursor (i.e., the hard carbon material body) was purchased from outside. The main component of the hard carbon material body is carbon atoms, the carbon layer thickness is 0.385nm, the particle size D50 is 5.6μm, and the tap density is 0.72g / cm 3 , with a specific surface area of ​​3.2m 2 / g, the discharge capacity is 338.2mAh / g, and the first efficiency is 82.5%.

[0081] The coating layer precursor is purchased from outside. The main component of the coating layer precursor is the by-product obtained from the oil refinery, and its density is 1.15g / cm 3 , coking value is 18.0%, ash content is <0.05%, and moisture content is <0.1%.

[0082] Example 1

[0083] This embodiment provides a modified hard carbon material and a preparation method thereof, comprising the following steps:

[0084] (1) The coating layer precursor is added to the hard carbon precursor for wet fusion. The wet fusion equipment is a LHS-500 model 50L mechanical fusion machine. The mass ratio of the hard carbon precursor to the coating layer precursor is 1:0.03. The wet fusion time is 20 minutes. The speed of the wet fusion equipment is 900 r / min to obtain a hard carbon fusion material in a mechanically molten state.

[0085] (2) The hard carbon fusion material obtained in step (1) is put into a tunnel kiln and carbonized at 1000°C for 18 hours in an inert atmosphere to obtain a carbonized fusion material.

[0086] (3) The carbonized fusion material obtained in step (2) is mixed in an LH-8 ribbon mixer (volume 6m 3) The mixed materials are screened, the mixing time is 45 minutes, and the finished products are screened to obtain modified hard carbon materials.

[0087] In this embodiment, the particle size D50 of the modified hard carbon material finally obtained is 6.0 μm single particle, the particle size distribution range is 1.8 μm-24.0 μm, and the tap density is 0.80 g / cm 3 , with a specific surface area of ​​2.50m 2 / g, and the thickness of the coating layer of the modified hard carbon material is 10nm.

[0088] Example 2

[0089] This embodiment provides a modified hard carbon material and a preparation method thereof, which is different from Embodiment 1 in that: in step (1), the mass ratio of the hard carbon precursor to the coating layer precursor is 1:0.02.

[0090] In this embodiment, the particle size D50 of the modified hard carbon material finally obtained is a single particle of 5.9 μm, the particle size distribution range is 1.7 μm-23.4 μm, and the tap density is 0.81 g / cm 3 , with a specific surface area of ​​3.21m 2 / g, and the thickness of the coating layer of the modified hard carbon material is 2nm.

[0091] Example 3

[0092] This embodiment provides a modified hard carbon material and a preparation method thereof, which is different from Embodiment 1 in that: in step (1), the mass ratio of the hard carbon precursor to the coating layer precursor is 1:0.06.

[0093] In this embodiment, the particle size D50 of the modified hard carbon material finally obtained is a single particle of 6.4 μm, the particle size distribution range is 2.0 μm-25.4 μm, and the tap density is 0.8 g / cm 3 , with a specific surface area of ​​3.01m 2 / g, and the thickness of the coating layer of the modified hard carbon material is 30nm.

[0094] Example 4

[0095] This embodiment provides a modified hard carbon material and a preparation method thereof, which is different from Embodiment 1 in that the rotation speed of the wet fusion equipment in step (1) is 600 r / min.

[0096] In this embodiment, the particle size D50 of the modified hard carbon material finally obtained is a single particle of 5.8 μm, the particle size distribution range is 2.0 μm-24.5 μm, and the tap density is 0.81 g / cm 3 , with a specific surface area of ​​2.61m 2 / g, and the thickness of the coating layer of the modified hard carbon material is 14nm.

[0097] Example 5

[0098] This embodiment provides a modified hard carbon material and a preparation method thereof, which differs from Embodiment 1 in that: in step (2), a carbonized fusion material is obtained by constant temperature carbonization treatment at 1100° C. for 18 hours in an inert atmosphere.

[0099] In this embodiment, the particle size D50 of the modified hard carbon material finally obtained is 6.1 μm for a single particle, the particle size distribution range is 2.2 μm-24.6 μm, and the tap density is 0.82 g / cm 3 , with a specific surface area of ​​2.70m 2 / g, and the thickness of the coating layer of the modified hard carbon material is 11nm.

[0100] Example 6

[0101] This comparative example provides a modified hard carbon material and a preparation method thereof, which is different from Example 1 in that: in step (1), the wet fusion time is 10 min, and the rotation speed of the wet fusion equipment is 300 r / min.

[0102] In this comparative example, the particle size D50 of the modified hard carbon material finally obtained is a single particle of 5.8 μm, the particle size distribution range is 1.8 μm-22.3 μm, and the tap density is 0.78 g / cm 3 , with a specific surface area of ​​3.18m 2 / g, and the thickness of the coating layer of the modified hard carbon material is 5nm.

[0103] Example 7

[0104] This comparative example provides a modified hard carbon material and a preparation method thereof, which is different from Example 1 in that: in step (2), a carbonized fusion material is obtained by constant temperature carbonization treatment at 1100° C. for 10 h in an inert atmosphere.

[0105] In this comparative example, the particle size D50 of the modified hard carbon material finally obtained is 5.7 μm for a single particle, the particle size distribution range is 1.8 μm-22.3 μm, and the tap density is 0.76 g / cm 3 , with a specific surface area of ​​3.22m 2 / g, and the thickness of the coating layer of the modified hard carbon material is 7nm.

[0106] Example 8

[0107] This comparative example provides a modified hard carbon material and a preparation method thereof, which is different from Example 1 in that: in step (1), the coating layer precursor is replaced by liquid petroleum asphalt. Liquid petroleum asphalt is commercially available from Liaoning Xinde New Materials Technology Co., Ltd., with a coking value of 25%-40% and a density of 1.13 g / cm 3, ash content <0.05%, moisture content <0.1%.

[0108] In this comparative example, the particle size D50 of the modified hard carbon material finally obtained is a single particle of 6.8 μm, the particle size distribution range is 2.5 μm-28.0 μm, and the tap density is 0.74 g / cm 3 , with a specific surface area of ​​3.45m 2 / g, and the thickness of the coating layer of the modified hard carbon material is 9nm.

[0109] Comparative Example 1

[0110] This comparative example provides a hard carbon material and a preparation method thereof, which is different from Example 1 in that in step (1), no nano precursor is added to the hard carbon precursor, and the hard carbon precursor is directly wet-fused.

[0111] In this comparative example, the particle size D50 of the hard carbon material finally obtained is a single particle of 5.6 μm, the particle size distribution range is 1.5 μm-20 μm, and the tap density is 0.72 g / cm 3 , the specific surface area is 4.53.2m 2 / g, and the thickness of the nano-coating layer of the hard carbon material is 0nm.

[0112] Comparative Example 2

[0113] This comparative example provides a modified hard carbon material and a preparation method thereof, which is different from Example 1 in that the hard carbon precursor in step (1) is replaced by natural graphite. Natural graphite is commercially available and purchased from Shenzhen Bettery New Energy Materials Co., Ltd.

[0114] In this comparative example, the modified hard carbon material finally obtained has a spherical particle size D50 of 7.3 μm, a particle size distribution range of 2.5 μm-26.4 μm, and a tap density of 0.93 g / cm 3 , with a specific surface area of ​​2.9m 2 / g, discharge capacity is 360.4mAh / g, first efficiency is 93.2%, and the thickness of the nano-coating layer of the graphite material is 8nm.

[0115] Comparative Example 3

[0116] This comparative example provides a hard carbon material and a preparation method thereof, which is different from Example 1 in that the mass ratio of the hard carbon precursor to the nano precursor in step (1) is 1:0.08.

[0117] In this comparative example, the particle size D50 of the hard carbon material finally obtained is a single particle of 6.6 μm, the particle size distribution range is 1.5 μm-20 μm, and the tap density is 0.72 g / cm 3 , with a specific surface area of ​​4.5m 2 / g, and the thickness of the nano-coating layer of the hard carbon material is 50nm.

[0118] Comparative Example 4

[0119] This comparative example provides a modified hard carbon material and a preparation method thereof, which is different from Example 1 in that: in step (1), the nano precursor is replaced by solid petroleum asphalt. The solid petroleum asphalt is commercially available from Liaoning Xinde New Materials Technology Co., Ltd., and has a softening point of 160°C-240°C and a coking value of 40%-60%.

[0120] In this comparative example, the particle size D50 of the modified hard carbon material finally obtained is 6.9 μm for a single particle, the particle size distribution range is 2.7 μm-26.8 μm, and the tap density is 0.7 g / cm 3 , with a specific surface area of ​​3.9m 2 / g, the nano-coating layer of the modified hard carbon material is a point-like coating, and the coating is uneven, and the maximum thickness of the coating layer is 80nm.

[0121] In order to illustrate the modified hard carbon material provided in Example 1, the following tests were performed:

[0122] The modified hard carbon materials / hard carbon materials obtained in Examples 1 to 8 and Comparative Examples 1 to 4 were subjected to XRF testing, and the testing instrument used was an XRF-1800 wavelength dispersive X-ray fluorescence spectrometer. The content ratio of carbon element in the modified hard carbon material, that is, the ratio of the mass of carbon element in the overall mass of the modified hard carbon material, was obtained; the D50 of the modified hard carbon material was tested using a laser particle size distribution instrument Dandong Better BT-3000Plus; the tap density of the modified hard carbon material was tested using a tap density tester HT-100A; the surface morphology of the modified hard carbon material was tested using a German Zeiss field emission scanning electron microscope SIGMA500; the specific surface area of ​​the modified hard carbon material was tested using a specific surface tester V-sorb 2800; the thickness of the nano-coating layer in the modified hard carbon material was tested using a JEM-2100F field emission transmission electron microscope, and the corresponding test results are shown in Table 1 below:

[0123] Table 1

[0124]

[0125] The modified hard carbon materials prepared in Examples 1 to 8 and Comparative Examples 1 to 4 were assembled into lithium ion button half cells, and the charge and discharge capacities were tested.

[0126] The half-cell test method is as follows: modified hard carbon material, carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber are mixed in water at a mass ratio of 100:1:1.2:2 to form a negative electrode slurry, which is evenly coated on copper foil using an applicator, and the pole piece is placed in a vacuum drying oven at a temperature of 105°C for vacuum drying for 12 hours, and rolled to form a negative electrode. CR-2025 button-type lithium-ion batteries are assembled in an argon-filled glove box, with lithium sheets as counter electrodes, polypropylene diaphragms, 1M LiPF6 solution as the electrolyte, and ethylene carbonate (EC) and dimethyl carbonate (DMC) with a volume ratio of 1:1 as solvents.

[0127] The CT2001A battery testing system of Wuhan Blue Electric Electronics Co., Ltd. conducted the first efficiency performance test. In the first week, the battery was discharged at a constant current of 0.1C to 0.05mV, then discharged at a constant voltage with a cut-off current of 0.005C, and then charged at a constant current of 0.1C to 1.5V. This was repeated three times in sequence, and the specific capacity of the third discharge was taken as the discharge specific capacity of the modified hard carbon material.

[0128] The modified hard carbon materials prepared in Examples 1 to 8 and Comparative Examples 1 to 4 were assembled into soft-pack lithium-ion batteries, and full-battery tests were performed.

[0129] The full battery test method is as follows: the modified hard carbon material prepared in the embodiments of the present invention and the comparative examples is used as the negative electrode, and lithium iron phosphate, PVDF, conductive carbon black and solvent NMP with a mass ratio of 96:1.5:2.5 are mixed and coated on a 15μm thick aluminum foil. The positive and negative electrode sheets after coating and baking are subjected to rolling, sheeting, lamination, drying, liquid injection, sealing, formation, high temperature aging, capacity division and other processes to make a 2.0Ah soft-pack lithium-ion battery, and the first efficiency, low temperature (-10°C) resistance, and high temperature (45°C) cycle performance of the soft-pack lithium-ion battery are tested.

[0130] The first efficiency test method is: charge at 0.05C constant current for 180min, stand for 15min, charge at 0.15C constant current for 300min, stand for 15min, charge at 0.3C constant current and constant voltage to 3.8V, cut-off current 0.05C, stand for 15min; discharge at 1C constant current to 2.0V.

[0131] -10℃ charging 3C voltage difference test method: the battery is discharged at 1C constant current to 2.0V, and left for 30min; the battery is charged at 1C constant current for 30min to 50% SOC, the upper limit voltage is 3.8V, and left for 4H; the battery cabinet is frozen at -10 degrees for more than 6h; the battery is charged at 3C constant current for 30s (data acquisition frequency is 100ms). This test method is used to characterize the lithium insertion kinetics of materials at low temperatures.

[0132] -10℃ contact impedance Rs test method: the battery is discharged at 1C constant current to 2.0V and left for 30min; the battery is charged at 1C to 50% SOC; the battery is frozen in a -10℃ constant temperature box for more than 6h; the EIS frequency range is 10000~0.01Hz. This test method is used to characterize the intrinsic contact conductivity of materials at low temperatures.

[0133] -10℃ charge transfer impedance Rct test method: the battery is discharged at 1C constant current to 2.0V and left for 30min; the battery is charged at 1C to 50% SOC; the battery is frozen in a -10℃ constant temperature box for more than 6h; the EIS test is performed: the frequency range is 10000~0.01Hz. This test method is used to characterize the interface dynamics of materials at low temperatures.

[0134] High temperature (45°C) cycle performance test method: discharge at 1C constant current to the lower limit voltage at room temperature, and leave for 30 minutes; place the battery in a high temperature environment of 45°C and leave for 2 hours; charge the battery at 1C constant current and constant voltage to the upper limit voltage, cut off at 0.05C, and leave for 30 minutes; discharge the battery at 1C constant current to the lower limit voltage, leave for 30 minutes, record the 1C discharge capacity and median voltage; repeat steps 3-4 250 times. This test method is used to characterize high temperature kinetics and interface side reaction characteristics.

[0135] The test results are shown in Table 2 below:

[0136] Table 2

[0137]

[0138] analyze Figure 1 From the electron microscope image, it can be seen that the modified hard carbon material after coating appears as blocky particles with relatively sharp and angular surfaces and small fine powder particles attached.

[0139] By analyzing Table 1 and Table 2 and comparing Example 1 with Comparative Example 1, it can be obtained that the first efficiency of Example 1 is significantly improved compared with Comparative Example 1, indicating that liquid phase coating (using liquid phase nano-coating layer precursor) can improve the surface micropores and active functional group structure of the hard carbon substrate, and the first Coulomb efficiency of the obtained material is significantly improved.

[0140] Analysis of Table 1 and Table 2 comparing Example 1 with Comparative Example 1 and Comparative Example 4 shows that compared with the hard carbon substrate not coated with the nano-coating layer and the hard carbon substrate coated with solid phase asphalt, the low-temperature charge transfer impedance Rct and low-temperature charging voltage difference of the modified hard carbon material of Example 1 are significantly reduced, and the interface dynamics are significantly improved. This is because the uniform and appropriate nano-coating layer on the particle surface can improve the interface transmission performance; the surface solid-phase carbon coating process in Comparative Example 4 has uneven deposition of the surface carbon structure in the micropores and more interface side reactions, which is not conducive to the improvement of the first efficiency and rate.

[0141] By analyzing Table 1 and Table 2 and comparing Example 1, Example 3 and Comparative Example 3, it can be obtained that when the mass ratio of the hard carbon precursor and the nano precursor is controlled within a reasonable range, the thickness of the coating layer is appropriate, and an excellent coating effect is achieved, which is beneficial to improving the low-temperature power of the modified hard carbon material, and the first efficiency and high-temperature cycle are also significantly improved.

[0142] Analysis of Table 1 and Table 2 comparing Example 1 and Comparative Example 2 shows that hard carbon has superior low-temperature kinetic properties compared to graphite, mainly because hard carbon has a larger interlayer spacing and an optimized interface lithium diffusion structure; Figure 3 It can be seen that modified hard carbon is also beneficial to improve the recognition of charge and discharge voltages and to identify the remaining power of the battery.

[0143] By comparing Tables 1 and 2 with Example 1 and Example 4, it can be found that the wet fusion time greater than 15 minutes and the wet fusion equipment speed greater than 600 r / min can make the nano-coating layer adhere to and melt on the surface of the hard carbon substrate to a large extent, and the optimized fusion process greatly improves the feasibility of mass production. By comparing Example 1 and Example 6, it can be found that the short wet fusion time or the low wet fusion speed leads to weak friction between the surface of the hard carbon precursor and the liquid nano-precursor, poor adhesion and melting, limited improvement in the first Coulomb efficiency of the material, and limited improvement in the high-temperature cycle capacity retention rate.

[0144] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship of the accompanying drawings, which are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or original referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.

[0145] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiment and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. A modified hard carbon material, characterized in that: include: A hard carbon substrate, which exists in solid form at room temperature; The coating layer is coated on the outer surface of the hard carbon substrate, and the thickness of the coating layer is 1nm-40nm.

2. The modified hard carbon material according to claim 1, characterized in that The coating layer is a soft carbon material, the carbon layer structure of the coating layer is a disordered carbon layer stack, and the carbon layer spacing of the coating layer is 0.34nm-0.37nm.

3. The modified hard carbon material according to claim 1 or 2, characterized in that: The particle size D50 of the modified hard carbon material is 3.5 μm-8.5 μm; and / or The tap density of the modified hard carbon material is 0.6 g / cm 3 -0.9g / cm 3 ; and / or The specific surface area of ​​the modified hard carbon material is 2.5 m 2 / g-4m 2 / g.

4. A hard carbon fusion material, characterized in that: include: Hard carbon precursor, which exists in solid form at room temperature; A coating layer precursor exists in liquid form at room temperature, the coating layer precursor is coated on the outer surface of the hard carbon precursor, and the mass ratio of the hard carbon precursor to the coating layer precursor is 1:(0.02-0.06); The hard carbon fusion material is carbonized to form the modified hard carbon material according to any one of claims 1 to 3, wherein the hard carbon precursor is carbonized to form a hard carbon substrate, and the coating layer precursor is carbonized to form a coating layer.

5. The hard carbon fusion material according to claim 4, characterized in that: The particle size D50 of the hard carbon precursor is 3 μm-8.56 μm; and / or The tap density of the hard carbon precursor is 0.85 g / cm 3 -1g / cm 3 ; and / or The specific surface area of ​​the hard carbon precursor is 2 m 2 / g-4m 2 / g.

6. The hard carbon fusion material according to claim 4, characterized in that: The density of the coating layer precursor is 1.05 g / cm 3 -1.25g / cm 3 ; and / or The coking value of the coating layer precursor is 12%-24%; and / or The ash content of the coating layer precursor is less than or equal to 0.15%; and / or The moisture content of the coating layer precursor is less than or equal to 0.3%.

7. A method for preparing a modified hard carbon material, characterized in that: include: Mixing the coating layer precursor with the hard carbon precursor to obtain a hard carbon fusion material; The hard carbon fusion material is carbonized to obtain a modified hard carbon material, wherein the hard carbon precursor is carbonized to form a hard carbon substrate, and the coating layer precursor is carbonized to form a coating layer.

8. The method for preparing a modified hard carbon material according to claim 7, characterized in that: The mixing time of the coating layer precursor and the hard carbon precursor is 5 min-40 min, and the mixing rotation speed of the coating layer precursor and the hard carbon precursor is 200 r / min-1500 r / min.

9. The method for preparing a modified hard carbon material according to claim 7, characterized in that: The hard carbon fusion material is subjected to the carbonization treatment in an inert atmosphere, the temperature of the carbonization treatment is 800° C.-1450° C., and the time of the carbonization treatment is 5 h-22 h.

10. A negative electrode plate, characterized in that: It comprises a negative electrode current collector and the modified hard carbon material as described in any one of claims 1 to 3, or comprises a negative electrode current collector and the modified hard carbon material prepared as described in any one of claims 7 to 9, wherein the modified hard carbon material is attached to the negative electrode current collector.

11. A battery, characterized in that: It comprises a positive electrode sheet, a separator and the negative electrode sheet as claimed in claim 10, wherein the positive electrode sheet and the negative electrode sheet are stacked, and the separator is placed between the positive electrode sheet and the negative electrode sheet.

12. An electrical device, characterized in that: Comprising the battery of claim 11.